Highly sensitive cardiac troponin T and long-term mortality in a population of community-derived perimenopausal women: nested case-control study. Issue 8 (12th January 2013) - Cramer, G Etienne; Brouwer, Marc A; Vader, Huib L; de Boer, Menko Jan; Pop, Gheorghe A M; Pop, Victor J M; Verheugt, Freek W A
Abstract : Objective: To assess the association between baseline levels of highly sensitive cardiac troponin T (hs-cTnT) and long-term mortality in perimenopausal women of the general community using a gender specific 99th percentile reference limit. Design: Nested case control. Setting: The present study was conducted within the Eindhoven Perimenopausal Osteoporosis Study which is a large prospective cohort of 8503 community-derived women of the city of Eindhoven, The Netherlands. Participants: Cases were defined as Eindhoven Perimenopausal Osteoporosis Study participants who provided an adequate baseline blood sample and subsequently experienced death during follow-up between 1994 and 2003. In total, 123 cases were identified. For each case two matched controls were selected using age, body mass index and hypertension as matching factors. The gender specific 99th percentile reference limit determined in the 246 controls was 8.0 ng/l. Main outcome measure: All cause mortality. Results: Hs-cTnT was significantly higher in the cases: 3.0 ng/l versus 2.3 ng/l (p=0.04). After adjustment for matching and clinical risk factors, each 1 SD increase of the level of hs-cTnT was significantly associated with mortality (OR 1.3, 95% CI 1.1 to 1.7, p=0.018). With amino-terminal pro-B-type natriuretic peptide (NT-proBNP) in the multivariable model as a continuous variable the association of hs-cTnT with mortality was lost. With both hs-cTnT and NT-proBNP as dichotomous variables, the gender specific 99th percentile reference limit (8.0 ng/l) was associated with mortality, independent of NT-proBNP (OR 3.7, 95% CI 1.0 to 13.2, p=0.048). Conclusions: In this study of community-derived perimenopausal women, hs-cTnT was associated with long-term mortality, independent of clinical risk factors. With the use of easily applicable cut-off levels, the gender specific reference limit of hs-cTnT had a prognostic impact that was independent of NT-proBNP.